Efficient sensing of hydrogen peroxide via electrocatalytic oxidation reactions using polycrystalline Au electrode modified with controlled thiol group immobilization. (1st November 2021) - Dutta, Anim; Hasan, Md. Mahmudul; Miah, Md. Rezwan; Nagao, Yuki; Hasnat, Mohammad A.
Abstract: Hydrogen peroxide is widely used in various industries for the synthesis of different chemicals and often applied as a fuel in fuel cells instead of oxygen. Thus, quick detection of hydrogen peroxide is important, and consequently the development of a cost-saving methodology is a time-worthy necessity. A Polycrystalline Au [Au(pc)] electrode does not show significant electrocatalytic performance concerning H2 O2 oxidation reaction. The catalytic performance is improved tremendously while Au(110) and Au(100) sites of Au(pc) surface are selectively blocked with the thiol group adsorption keeping Au(111) sites unblocked in an alkaline medium. In this article, cysteine molecules were used as the source of the thiol functional group which has coverage on Au(111) with a value of 3.47 × 10 −10 mol cm −2 . While Cysteine molecules are partially adsorbed on Au(110) and Au(100) sites, the unblocked Au(111) sites receive a partially positive charge, which is assumed to catalyze the oxidation of anionic species ( HO 2 − ) . The current response vs H2 O2 concentration relationship showed a wide linear dynamic range (LDR) between 1 and 3000 µM with LOD of 0.8 µM having a sensitivity of 58.68 µA mM −1 cm −2 . In this article, detailed electrochemical investigations and characterizations of the developed sensor have been attained using cyclic voltammetric (CV), square wave voltammetric (SWV), and amperometric techniques.